Physically based crystal plasticity modelling of nano-indentation - Liang, H; Dunne, F; Wilkinson, A (2008)
A physically based 3D, large deformation implicit crystal plasticity model has been developed and implemented within an ABAQUS user-defined finite element to enable incorporation of length scale effects by relating the absolute GND density to plastic strain gradient. The 3D crystal slip model has been used to model the iron nanoindentation experiments of Randmand et al. [1]. Hardness - indentation depth curves with and without the inclusion of GND density incorporated in the model have been investigated and compared with the experiments. The model is shown to predict correctly the progressive decrease in hardness with increasing indentation depth.